Advances in wide bandgap SiC for optoelectronics - Ou, Haiyan; Ou, Yiyu; Argyraki, Aikaterini; Schimmel, Saskia; Kaiser, Michl; Wellmann, Peter; Linnarsson, Margareta K.; Jokubavicius, Valdas; Sun, Jianwu; Liljedahl, Rickard; Syväjärvi, Mikael (European Physical Journal B, 2014)
Silicon carbide (SiC) has played a key role in power electronics thanks to its unique physical properties like wide bandgap, high breakdown field, etc. During the past decade, SiC is also becoming more and more active in optoelectronics thanks to the progress in materials growth and nanofabrication. This paper will review the advances in fluorescent SiC for white light-emitting diodes, covering the polycrystalline doped SiC source material growth, single crystalline epitaxy growth of fluorescent SiC, and nanofabrication of SiC to enhance the extraction efficiency for fluorescent SiC based white LED
Keywords: SiC; wide bandgap; fluorescence

Broadband and omnidirectional light harvesting enhancement of fluorescent SiC - Ou, Yiyu; Jokubavicius, Valdas; Hens, Philip; Kaiser, Michl; Wellmann, Peter; Yakimova, Rositza; Syväjärvi, Mikael; Ou, Haiyan (Optics Express, 2012)
In the present work, antireflective sub-wavelength structures have been fabricated on fluorescent 6H-SiC to enhance the white light extraction efficiency by using the reactive-ion etching method. Broadband and omnidirectional antireflection characteristics show that 6H-SiC with antireflective sub-wavelength structures suppress the average surface reflection significantly from 20.5 % to 1.01 % over a wide spectral range of 390-784 nm. The luminescence intensity of the fluorescent 6H-SiC could be enhanced in the whole emission angle range. It maintains an enhancement larger than 91 % up to the incident angle of 70 degrees, while the largest enhancement of 115.4 % could be obtained at 16 degrees. The antireflective sub-wavelength structures on fluorescent 6H-SiC could also preserve the luminescence spectral profile at a large emission angle by eliminating the Fabry-Perot microcavity interference effect. (C) 2012 Optical Society of America
Keywords: Nanostructure fabrication; Photoluminescence; Subwavelength structures; Nanostructures.

Carrier Lifetimes and Influence of In-Grown Defects in N-B Co-Doped 6H-SiC - Grivickas, Vytautas; Gulbinas, Karolis; Jokubavicius, Valdas; Sun, Jianwu; Karaliūnas, Mindaugas; Kamiyama, Satoshi; Linnarsson, Margareta K.; Kaiser, Michl; Wellmann, Peter; Syväjärvi, Mikael (IOP Conference Series: Materials Science and Engineering, 2014)
The thick N-B co-doped epilayers were grown by the fast sublimation growth method and the depth-resolved carrier lifetimes have been investigated by means of the free-carrier absorption (FCA) decay under perpendicular probe-pump measurement geometry. In some samples, we optically reveal in-grown carbon inclusions and polycrystalline defects of substantial concentration and show that these defects slow down excess carrier lifetime and prevent donor-acceptor pair photoluminescence (DAP PL). A pronounced electron lifetime reduction when injection level approaches the doping level was observed. It is caused by diffusion driven non-radiative recombination. However, the influence of surface recombination is small and insignificant at 300
Keywords: SiC; sublimation growth; carrier lifetime; co-doped epilayers

Effects of source material on epitaxial growth of fluorescent SiC - Jokubavicius, V.; Hens, Philip; Liljedahl, R.; Sun, J. W.; Kaiser, Michl; Wellmann, Peter; Sano, S.; Yakimova, R.; Kamiyama, S.; Syväjärvi, Mikael (Thin Solid Films, 2012)
The growth of fluorescent SiC using Fast Sublimation Growth Process was demonstrated using different types of SiC source materials. These were prepared by (i) high-temperature hot pressing, (ii) chemical vapor deposition and (iii) physical vapor transport. The optimized growth rates of 50 mu m/h, 170 mu m/h and 200 mu m/h were achieved using the three types of sources, respectively. The best results in respect to growth rates are obtained using higher density sources. Fluorescent SiC layers with mirror-like morphology, very good crystal quality and yellowish or warm white light photoluminescence at room temperature were grown using all three types of the source materials. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Sublimation growth; Fluorescence; Photoluminescence; Silicon carbide

Fabrication of broadband antireflective sub-wavelength structures on fluorescent SiC - Ou, Yiyu; Jokubavicius, Valdas; Kaiser, Michl; Wellmann, Peter; Linnarsson, Margareta K.; Yakimova, Rositsa; Syväjärvi, Mikael; Ou, Haiyan (Materials Science Forum, 2013)
Surface nanocones on 6H-SiC have been developed and demonstrated as an effective method of enhancing the light extraction efficiency from fluorescent SiC layers. The surface reflectance, measured from the opposite direction of light emission, over a broad bandwidth range is significantly suppressed from 20.5% to 1.0 % after introducing the sub-wavelength structures. An omnidirectional light harvesting enhancement (>91%), is also achieved which promotes fluorescent SiC as a good candidate of wavelength converter for white light-emitting diode
Keywords: Fluorescent SiC; Nanostructures fabrication; Photoluminescence; donor-acceptor-pair emission

Fluorescent SiC as a new material for white LEDs - Syväjärvi, Mikael; Müller, Julian; Sun, J. W.; Grivickas, V.; Ou, Yiyu; Jokubavicius, V.; Hens, Philip; Kaiser, Michl; Ariyawong, K.; Gulbinas, K.; Liljedahl, R.; Linnarsson, M. K.; et al. (Physica Scripta, 2012)
Current III-V-based white light-emitting diodes (LEDs) are available. However, their yellow phosphor converter is not efficient at high currents and includes rare-earth metals, which are becoming scarce. In this paper, we present the growth of a fluorescent silicon carbide material that is obtained by nitrogen and boron doping and that acts as a converter using a semiconductor. The luminescence is obtained at room temperature, and shows a broad luminescence band characteristic of donor-to-acceptor pair recombination. Photoluminescence intensities and carrier lifetimes reflect a sensitivity to nitrogen and boron concentrations. For an LED device, the growth needs to apply low-off-axis substrates. We show by ultra-high-resolution analytical transmission electron microscopy using aberration-corrected electrons that the growth mechanism can be stable and that there is a perfect epitaxial relation from the low-off-axis substrate and the doped layer even when there is step-bunching.
Keywords: Silicon Carbide; SiC; Fluorescence; white LED

Lateral boron distribution in polycrystalline SiC source materials - Linnarsson, Margareta K.; Kaiser, Michl; Liljedahl, Rickard; Jokubavicius, Valdas; Ou, Yiyu; Wellmann, Peter; Ou, Haiyan; Syväjärvi, Mikael (Materials Science Forum, 2013)
Polycrystalline SiC containing boron and nitrogen are used in growth of fluorescent SiC for white LEDs. Two types of doped polycrystalline SiC have been studied in detail with secondary ion mass spectrometry: sintered SiC and poly-SiC prepared by sublimation in a physical vapor transport setup. The materials are co-doped materials with nitrogen and boron to a concentration of 1x10(18) cm(-3) and 1x10(19) cm(-3), respectively. Depth profiles as well as ion images have been recorded. According to ocular inspection, the analyzed poly-SiC consists mainly of 4H-SiC and 6H-SiC grains. In these grains, the boron concentration is higher and the nitrogen concentration is lower in the 6H-SiC compared to the 4H-SiC polytype. No inter-diffusion between grains is observe
Keywords: Boron; Dopant Distribution; SIMS

Modeling of the mass transport during the homo-epitaxial growth of silicon carbide by fast sublimation epitaxy - Hupfer, Thomas; Hens, Philip; Kaiser, Michl; Jokubavicius, Valdas; Syväjärvi, Mikael; Wellmann, Peter (Materials Science Forum, 2013)
Two growth regions with different limitation of growth speed are observed in the fast sublimation growth process of silicon carbide. Using suggested theoretical model for the mean free path calculations, the influences of temperature and inert gas pressure on the mass transport for the growth of epitaxial layers were considered theoretically and confirmed by experimental data. © (2013) Trans Tech Publications, Switzerlan
Keywords: Mass Transport; Modeling; Silicon Carbide (SiC); Sublimation Epitaxy

Morphological and optical stability in growth of fluorescent SiC on low off-axis substrates - Jokubavicius, Valdas; Kaiser, Michl; Hens, Philip; Wellmann, Peter; Liljedahl, Rickard; Yakimova, Rositsa; Syväjärvi, Mikael (Materials Science Forum, 2013)
Fluorescent silicon carbide was grown using the fast sublimation growth process on low off-axis 6H-SiC substrates. In this case, the morphology of the epilayer and the incorporation of dopants are influenced by the Si/C ratio. Differently converted tantalum foils were introduced into the growth cell in order to change vapor phase stochiometry during the growth. Fluorescent SiC grown using fresh and fully converted tantalum foils contained morphological instabilities leading to lower room temperature photoluminescence intensity while an improved morphology and optical stability was achieved with partly converted tantalum foil. This work reflects the importance of considering the use of Ta foil in sublimation epitaxy regarding the morphological and optical stability in fluorescent silicon carbid
Keywords: fluorescent SiC; low off-axis substrates; sublimation epitaxy

Nucleation and growth of polycrystalline SiC - Kaiser, Michl; Schimmel, Saskia; Jokubavicius, Valdas; Linnarsson, Margareta K.; Ou, Hayan; Syväjärvi, Mikael; Wellmann, Peter (IOP Conference Series: Materials Science and Engineering, 2014)
The nucleation and bulk growth of polycrystalline SiC in a 2 inch PVT setup using isostatic and pyrolytic graphite as substrates was studied. Textured nucleation occurs under near-thermal equilibrium conditions at the initial growth stage with hexagonal platelet shaped crystallites of 4H, 6H and 15R polytypes. It is found that pyrolytic graphite results in enhanced texturing of the nucleating gas species. Reducing the pressure leads to growth of the crystallites until a closed polycrystalline SiC layer containing voids with a rough surface is developed. Bulk growth was conducted at 35 mbar Ar pressure at 2250 degrees C in diffusion limited mass transport regime generating a convex shaped growth form of the solid-gas interface leading to lateral expansion of virtually [001] oriented crystallites. Growth at 2350 degrees C led to the stabilization of 6H polytypic grains. The micropipe density in the bulk strongly depends on the substrate use
Keywords: fluorescent SiC; PVT; nucleation; polycristalline growth

Photoluminescence topography of fluorescent SiC and its corresponding source crystals - Wilhelm, Martin; Kaiser, Michl; Jokubavicius, Valdas; Syväjärvi, Mikael; Ou, Yiyu; Ou, Haiyan; Wellmann, Peter (Materials Science Forum, 2013)
The preparation and application of co-doped polycrystalline SiC as source in sublimation growth of fluorescent layers is a complex topic. Photoluminescence topographies of luminescent 6H-SiC layers and their corresponding source crystals have been studied in order to investigate the dependence of the epitaxial growth on the source material. It is shown that the homogeneity concerning the dopant incorporation and the layer luminescence intensity does not depend on the characteristics of the PVT grown source material. Therefore co-doped polycrystalline SiC is a promising source material in fast sublimation growth of luminescent 6H-Si
Keywords: luminescent SiC; 6H-SiC; epitaxy; photoluminescence topography

Polycrystalline SiC as source material for the growth of fluorescent SiC layers - Kaiser, Michl; Hupfer, Thomas; Jokubavicius, Valdas; Schimmel, Saskia; Syväjärvi, Mikael; Ou, Yiyu; Ou, Haiyan; Linnarsson, Margareta K.; Wellmann, Peter (Materials Science Forum, 2013)
Polycrystalline doped SiC act as source for fluorescent SiC. We have studied the growth of individual grains with different polytypes in the source material. We show an evolution and orientation of grains of different polytypes in polycrystalline SiC ingots grown by the Physical Vapor Transport method. The grain influence on the growth rate of fluorescent SiC layers grown by a sublimation epitaxial process is discussed in respect of surface kinetic
Keywords: Silicon Carbide; Orientation; PVT; Polycrystalline; Doping

Step-flow growth of fluorescent 4H-SiC layers on 4 degree off-axis substrates - Schimmel, Saskia; Kaiser, Michl; Hens, Philip; Jokubavicius, Valdas; Liljedahl, Rickard; Sun, Jianwu; Yakimova, Rositsa; Ou, Yiyu; Ou, Haiyan; Linnarsson, Margareta K.; Wellmann, Peter; Syväjärvi, Mikael (Materials Science Forum, 2013)
Homoepitaxial layers of fluorescent 4H-SiC were grown on 4 degree off-axis substrates by sublimation epitaxy. Luminescence in the green spectral range was obtained by co-doping with nitrogen and boron utilizing donor-acceptor pair luminescence. This concept opens possibilities to explore green light emitting diodes using a new materials platfor
Keywords: fluorescent silicon carbide; sublimation epitaxy; co-doping; donor-acceptor pair luminescence; light conversion

The role of defects in fluorescent silicon carbide layers grown by sublimation epitaxy - Schimmel, Saskia; Kaiser, Michl; Jokubavicius, Valdas; Ou, Yiyu; Hens, Philip; Linnarsson, Margareta K.; Sun, J.; Liljedahl, Rickard; Ou, Haiyan; Syväjärvi, Mikael; Wellmann, Peter (IOP Conference Series: Materials Science and Engineering, 2014)
Donor-acceptor co-doped SiC is a promising light converter for novel monolithic all-semiconductor white LEDs due to its broad-band donor-acceptor pair luminescence and potentially high internal quantum efficiency. Besides sufficiently high doping concentrations in an appropriate ratio yielding short radiative lifetimes, long nonradiative lifetimes are crucial for efficient light conversion. The impact of different types of defects is studied by characterizing fluorescent silicon carbide layers with regard to photoluminescence intensity, homogeneity and efficiency taking into account dislocation density and distribution. Different doping concentrations and variations in gas phase composition and pressure are investigated.
Keywords: SiC; fluorescence; sublimation epitaxy